LO73: Long-term functional outcome and health-related quality of life of elderly out-of-hospital cardiac arrest survivors. (15th May 2017) - Mercier, E.; Andrew, E.; Nehme, Z.; Lijovic, M.; Bernard, S.; Smith, K.
Abstract : Introduction: This study aims to describe the long-term functional outcome and health-related quality of life of elderly (≥65 years old) out-of-hospital cardiac arrest (OHCA) survivors in Victoria, Australia.Methods: Elderly OHCA patients who arrested between January 1 st, 2010 and December 31 st, 2014 were identified from the Victorian Ambulance Cardiac Arrest Registry (VACAR). Living status, Glasgow Outcome Scale-Extended (GOS-E), Euro-QoL (EQ-5D) and Twelve-item Short Form (SF-12) Health Survey were collected by telephone 12 months following the OHCA.Results: Emergency medical services attended on 14, 678 elderly OHCA during the study period, 6, 851 (46.7%) of which received a resuscitation attempt. Of these, 668 patients (9.8%) survived to hospital discharge. The mean age of the survivors was 75 (standard deviation (SD) 7.4) years and 504 (75.4%) were male. Eighty-five patients subsequently died within 12 months of their OHCA. A total of 483 patients were interviewed (response rate 82.9%). At 12 months, 313 responders (64.9%) were living at home without care. Most responders (n=324 (67.2%)) had a good long-term functional recovery with a GOS-E ≥7. The proportion of patients with a GOS-E≥7 progressively decreased with increasing age (65-74 years: 66.1%, 75-84 years: 53.0%, ≥85 years: 27.3%). On the EQ-5D, the majority of survivors reported no problem with mobility (n=266 (55.1%)), self-care (n=403 (83.4%)), activity (n=293 (60.6%)), pain (n=335 (69.3%)) and anxiety (n=358 (74.1%)). On the SF-12, the mean mental component summary was 56.3 (SD 6.6) while the mean physical component summary was 44.7 (SD 11.4) (both measures range from 0-100). Among the 1, 951 patients who arrested in a supported accommodation, 849 (43.5%) had a resuscitation attempt, and of these, 21 survived to hospital discharge (2.5%). Only eight (1.0%) of these patients were still alive 12 months after the OHCA and one survivor (0.12%) had a good functional outcome (GOS-E≥7).Conclusion: Most elderly OHCA survivors have an adequate long-term functional status and health-related quality of life. However, the likelihood of having a good functional recovery decreases with increasing age, and is rare for patients arresting in a supported accommodation.